Keterpikatan Kerja dan Kesejahteraan Pegawai Lintas Generasi di Indonesia - Sus Budiharto; Najmah Athirah (Psychopolytan : Jurnal Psikologi, 2024)
Research on employee well-being and work engagement in Indonesia is interesting. This study reports a literature review based on research on the relationship between these variables in cross-generational participants in Indonesia. The results show that employee well-being in Indonesia is reported in four constructs: employee well-being, well-being at work, subjective well-being, and psychological well-being. Work engagement in Indonesia is reported using two terms: work engagement and employee engagement. Many studies report that work engagement is a positive predictor of employee well-being, otherwise, several studies report the opposite, employee well-being becomes a positive predictor of work engagement. Several studies report the relationship between work engagement and employee well-being in participants across generations, from Z generation, millennials, and X, to the Boomer generation. Recommendations from this study include that future research can carry out model tests and mediator tests on variables that influence work engagement and employee welfare in Indonesia.